PERSUASION FROM BELOW?: An experimental assessment of the impact of anonymous comments sections. (16th November 2016) - Wallsten, Kevin; Tarsi, Melinda
Abstract : Guided by the belief that anonymity inevitably breeds the kind of uncivil discourse that hurts their readers, many news organizations have chosen to ban anonymous comments sections on their websites in recent years. Unfortunately, little empirical research has been conducted to assess whether exposure to anonymous comments actually does influence people's attitudes. In this paper, we address this oversight by asking: do anonymous comments posted on a newspaper website shape how internet users feel about the media? Using an online experiment to systematically manipulate exposure to anonymous comments attached to a "hard news" report, we find strong evidence that exposure to non-attributed posts—regardless of their tone—leads internet users to feel more negatively towards specific news organizations and the media in general.